Normal Cervical Effacement in Term Labor - Rhoades, Janine S.; Stout, Molly J.; Woolfolk, Candice; Tuuli, Methodius G.; Macones, George A.; Cahill, Alison G. (American Journal of Perinatology, 2019)
Objective To estimate the natural history of cervical effacement in labor.Study Design This is a retrospective cohort study of term, vertex, singletons who reached 10 cm of cervical dilation from 2010 to 2014. Interval-censored regression was used to estimate the median number of hours between changes in effacement (measured in centimeters of the residual cervix) and to estimate the median effacement at a given cervical dilation. Analysis was stratified by parity and labor type.Results In total, 7,319 patients were included. Multiparas had faster effacement from 1 cm to complete effacement than nulliparas, but nulliparas were significantly more effaced at each cervical dilation. Patients in spontaneous labor had faster effacement and were significantly more effaced at each centimeter of cervical dilation than those who were induced or augmented. Once active labor was established (>6 cm of cervical dilation), 95% of patients had an effacement of 1 cm or less. By 8 cm of cervical dilation, 50% of all patients were completely effaced.Conclusion There is a wide range in the normal length of time for the progression of cervical effacement. However, once a patient is in active labor, 95% of patients have effaced to 1 cm or less.
Keywords: effacement; labor; labor disorders; cervical effacement; first stage of labor; cervix